2013
DOI: 10.1139/bcb-2012-0065
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization and hemolytic properties of the C-terminal domain of pyolysin, a cholesterol-dependent cytolysin

Abstract: Pyolysin (PLO) belongs to the homologous family of the cholesterol-dependent cytolysins (CDCs), which bind to cell membranes containing cholesterol to form oligomeric pores of large size. The CDC monomer structure consists of four domains. Among these, the C-terminal domain 4 has been implicated in membrane binding of the monomer, while the subsequent processes of oligomerization and membrane insertion have primarily been assigned to other domains of the molecule.Recombinantly expressed or proteolytic fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Mixing of LLO D4 in ratios of 1:1, 2:1 and 3:1 (D4:WT) did not change the haemolytic activity of LLO WT ( Supplementary Fig. 3), whereas SLO D4 inhibited and PLO D4 amplified the activity of SLO 41 and PLO 43 , respectively.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Mixing of LLO D4 in ratios of 1:1, 2:1 and 3:1 (D4:WT) did not change the haemolytic activity of LLO WT ( Supplementary Fig. 3), whereas SLO D4 inhibited and PLO D4 amplified the activity of SLO 41 and PLO 43 , respectively.…”
Section: Resultsmentioning
confidence: 95%
“…PLO D4 also is able to bind to membranes 43 and to form straight arrays on cholesterol crystals 42 . In contrast to SLO D4, addition of PLO D4 to the full-length protein amplifies its haemolytic activity, whereas added LLO D4 does not, indicating that this domain probably does not integrate into the oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…A crystal structure of the PLO molecule presumably is homologous to the structure of other CDCs. The tertiary structure model of PLO, based on the perfringolysin O (PFO)—PLO sequence alignment—was proposed by Pokrajec et al [185]. The monomeric PLO molecule is rich in β-sheet elements and consists of four domains (D1 to D4), of which D2 and D3 are packed against each other, while D1 is located at the N -terminal and D4 at the C-terminal end of the molecule (Figure 4).…”
Section: Pathogenesis Of T Pyogenes Infectionmentioning
confidence: 99%
“…Although D4 was initially shown to interact between PFO monomers [54,55], subsequent studies indicated that D4 remains surrounded by water throughout the assembly of the pore [19,56]. More recently, however, Pokrajac et al [57] and Koster et al [4] showed that purified D4 from pyolysin and LLO, respectively, was capable of forming linear oligomeric arrays on liposomes. In contrast to the earlier work of Tweten et al [54] and Iwamoto et al [58] who showed an inhibitory effect of D4 on native toxin, Pokrajac et al showed that D4 increased pyolysin activity.…”
Section: Allosteric Pathway For Monomer Activationmentioning
confidence: 99%
“…Koster et al did not see an effect on LLO activity when it was mixed with purified D4. Pokrajac et al [57] further showed that mixing D4 with intact pyolysin resulted in cane-shaped oligomeric complexes on liposomes, which were presumably formed by the addition of native monomers to the ends of the D4 oligomers since the latter were not capable of forming circular oligomers. Taken together, these studies suggest that D4 may make transient contacts early in the assembly process, but its effect on the activity of native toxin remains unclear.…”
Section: Allosteric Pathway For Monomer Activationmentioning
confidence: 99%